New pyrimidine derivatives as potential agents against hepatocellular carcinoma: design, synthesis, and in vitro and in vivo biological evaluations - Bertrand, Jeanluc; Montorfano, Ignacio; Pérez-Castro, Ramón; Valdés-Valdés, Ricardo; Romero, Jacqueline; Delgado, Thalía; Brito, Iván; Santibáñez, Juan F.; Cabrera, Alan R.; Vieytes, María Paola; Echeverría, Javier; Salas, Cristian O.; et al. (Frontiers in Pharmacology, 2026)
BackgroundSorafenib is a tyrosine kinase inhibitor (TKI) used to treat hepatocellular carcinoma (HCC), but this drug causes clinically significant toxicities in approximately 50% of patients. Given the high frequency and severity of these side effects, it is necessary to develop new, safer drugs to treat this cancer.PurposeNovel 2,6,9-trisubstituted pyrimidine derivatives were synthesised and evaluated as potential antitumour agents for HCC.Materials and MethodsTwelve compounds (6a–l) were obtained by a four-step synthetic procedure using a simple and efficient methodology in which two key reactions were promoted by microwave irradiation. Subsequently, compounds 6a–l were evaluated in vitro for cytotoxic activity against the HCC cell line HepG2 and other cell lines; in vivo in the HepG2 xenograft tumour model; and in silico (docking and dynamic simulations).Results and discussionCompound 6e proved to be the most promising of this series (IC50 = 5.6 µM), as well as being more index selective than sorafenib and with lower cytotoxicity in Vero cells (18.92 µM). In addition, 6e was further evaluated in Huh-7 cells and demonstrated selectivity for HCC. Docking studies on the proposed targets, VEGFR-2 and B-raf, indicated that 6e could bind to them with binding energies and interaction patterns similar to those of sorafenib. The 6e interaction pattern at the VEGFR-2 binding site was corroborated by dynamic studies over 100 ns. A possible mechanism of 6e-induced HepG2 cell death was investigated. Experiments on caspases-3, -7, -8, -9, Apaf-1, Cyt-c, ERK1/2, and p53 showed that they were all activated, whereas Bcl-2 was inhibited by 6e in HepG2 cells. Furthermore, 6e induced the accumulation of reactive oxygen species (ROS) in HepG2 cells. These results suggest that apoptosis in HepG2 was caused by: (i) a caspase-dependent pathway and (ii) changes in the cellular levels of Bcl-2 family proteins and ROS. In addition, 6e attenuated the growth of HepG2 xenograft tumours in mice at a dose of 1 mg/kg for 3 weeks.ConclusionBased on these results, this pyrimidine derivative could be an interesting compound for the design of new agents against HCC.